2014
DOI: 10.1001/jama.2014.7184
|View full text |Cite
|
Sign up to set email alerts
|

Use of Whole-Exome Sequencing to Determine the Genetic Basis of Multiple Mitochondrial Respiratory Chain Complex Deficiencies

Abstract: Exome sequencing enhances the ability to identify potential nuclear gene mutations in patients with biochemically defined defects affecting multiple mitochondrial respiratory chain complexes. Additional study is required in independent patient populations to determine the utility of this approach in comparison with traditional diagnostic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
302
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 326 publications
(326 citation statements)
references
References 38 publications
9
302
1
2
Order By: Relevance
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…To date, 26 patients are reported with LTBL (12 by Steenweg et al (2012), one by Talim et al (2013), two by Taylor et al (2014), one by Biancheri et al (2015), one by Kohda et al (2016), one by Kevelam et al (2016), one by Danhauser et al (2016), one by Taskin et al (2016), one by G€ ung€ or et al (2016), two by Şahin et al (2016) and two by Pronicka et al (2016)), with our patient being the 26th reported patient. The phenotype of our patient fits the severe group of LTBL patients, mostly due to signs of perinatal presentation of the disease and rapid decline of her clinical status.…”
Section: Discussionmentioning
confidence: 61%
“…Although liver respiratory chain activity was normal, there was evident liver dysfunction. Liver involvement was also described in six additional EARS2 patients, which included one or more of neonatal transient icterus, hepatomegaly, fatty liver and steatosis (Steenweg et al 2012;Talim et al 2013;Taylor et al 2014;Pronicka et al 2016). Post-mortem examination of the liver from the patient reported by Talim et al (2013) also found COXdeficiency.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations